Vineyards characteristic by using GIS and refl ectance measurements on the Nagy-Eged hill in Hungary - Fórián, T.; Nagy, A.; Riczu, P.; Mézes, L.; Tamás, J. (International Journal of Horticultural Science, 2016)
Our investigation was carried out in vineyards on Nagy-Eged hill in Hungary. Grapevine growing plays an important role in Eger Vine Regions. In the grapevine cultivation it becomes necessary to know the requirements of vineyards along the best geographical situation using available cultivation and examination technology to achieve better and quality produce. This study reviews applicability of the different spatial analyst techniques in vineyard especially models based on surface relief and the new technology of hyperspectral analysis. The spectral alteration was examined between different health status and leaves infected by Eriophyes vitis to defi ne spectral characteristics. Thus reflectance measurements could also support to evaluate airborne hyperspectral images with the help of the spectral library.